Longitudinal Course of Disease in a Large Cohort of Myositis Patients With Autoantibodies Recognizing the Signal Recognition Particle - Pinal‐Fernandez, Iago; Parks, Cassie; Werner, Jessie L.; Albayda, Jemima; Paik, Julie J.; Danoff, Sonye K.; Casciola‐Rosen, Livia; Christopher‐Stine, Lisa; Mammen, Andrew L. (Arthritis care & research (2010), 2017)
Objective Patients with immune‐mediated necrotizing myopathy (IMNM) often have autoantibodies recognizing the signal recognition particle (SRP) or HMG‐CoA reductase (HMGCR). Here, we studied a cohort of anti‐SRP patients to identify factors associated with disease severity and clinical improvement; we also compared the severity of weakness in those with anti‐SRP versus anti‐HMGCR autoantibodies. Methods All anti‐SRP patients in the Johns Hopkins Myositis Cohort from 2002 to 2015 were included. Longitudinal information regarding proximal muscle strength, creatine kinase (CK) levels, and immunosuppressive therapy was recorded at each visit. Univariate and multivariate multilevel regression models were used to assess prognostic factors influencing recovery. Strength in the anti‐SRP patients was compared to strength in 49 previously described anti‐HMGCR subjects. Results Data from 37 anti‐SRP patients and 380 total clinic visits were analyzed. Younger age at onset was associated with more severe weakness at the first visit (P = 0.02) and all subsequent visits (P = 0.002). Only 50% of patients reached near‐full or full strength after 4 years of treatment, and most of these continued to have elevated CK levels. Rituximab appeared to be effective in 13 of 17 anti‐SRP patients. Anti‐SRP patients were significantly weaker than those with anti‐HMGCR autoantibodies (−1.3 strength points; P = 0.001). Conclusion Younger age at onset is associated with more severe weakness in anti‐SRP myositis. Furthermore, even among anti‐SRP patients whose strength improved with immunosuppression, most had ongoing disease activity as demonstrated by elevated CK levels. Finally, anti‐SRP patients were significantly weaker than anti‐HMGCR patients, providing evidence that these autoantibodies are associated with distinct forms of IMNM.